Influence of Lipid Transport System Gene Polymorphism on the Dyslipidemia and Coronary Lesions in Patients with Unstable Angina - Aziz S. Eshpulatov; S.U. Hashimov; Alexander B. Shek; Ravshanbek D. Kurbanov (International Journal of Biomedicine, 2015)
The purpose of this study was to identify the features of lipid metabolism and coronary lesions in view of the combined carrier of the ε4 allele of APOE ε2/ε3/ε4 polymorphism and the S2 allele of APOC3SstI polymorphism in UA patients. Materials and Methods: The study included 141 Uzbek patients with UA class IIB (Braunwald E. et al., 1989) who had coronary atherosclerosis of varying degrees, according to coronary angiography. The control group consisted of 50 healthy, age-matched, randomly selected Uzbek persons without clinical and instrumental signs of CHD according to the exercise test. Coronary angiography was performed using Allura CV-20 (Philips, Netherlands). Genotyping of the APOE (ε2/ε3/ε4) gene polymorphism and the APOC3 (SstI) gene polymorphism was performed by the PCR-RFLP method. Results: Our analysis revealed a significant prevalence of carriers of the S2 allele of APOC3SstI polymorphism and carriers of the ε4 allele of APOE ε2/ε3/ε4 polymorphism among UA patients compared to healthy ethnic Uzbeks. A combination of these two “damaging” alleles was observed in 26.2% of UA patients, which was accompanied by significantly higher blood levels of TC and LDL-C (P<0.05), a higher APOB/APOAI ratio (P<0.05), and a lower level of HDL-C (P<0.05). According to coronary angiography, a three-vessel lesion and more significantly predominated among these UA patients (OR: 2.25, 95% CI: 1.05-4.84, χ2=3.66, p<0.05).